Last to die : a novel - Gerritsen, Tess (Gerritsen, Tess. Rizzoli & Isles novel, 2012)
Visiting sixteen-year-old "Rat" Perkins at isolated Evenson boarding school, Maura Isles is astonished to learn that all of his classmates are survivors of violence and are being instructed in scientific detective skills, a discovery that coincides with Jane Rizzoli's investigation into the murder of a boy's foster family.